Biological nitrogen fixation and agronomic features of soybean (Glycine max (L.) Merr.) crop under different doses of inoculant (2018)
Soybean is one of the most important crops in the world and presents great versatility. This study aims to investigate the effect of the Bradyrhizobium japonicum inoculant at 0, 600 and 1200 mL ha-1 on soybean crop, with and without 1 L ha-1 calcium (Ca 41%) + 0.4 L ha-1 boron (B 14%). Plants were grown for 90 days in plastic pots with 3 kg of sand and vermiculite (v/v) autoclaved at 121oC for 1 h. The experiment was conducted in a completely randomized design with five replications in a greenhouse. Soybean yield parameters were evaluated, such as, dry weight of shoot, root and total; plant height, nitrogen in the shoot; number and dry weight of nodules; chlorophyll index in the leaves; number of pods per plant (NPPL); number of grains per pod (NGP); and number of grains per plant (NGPL). The addition of Ca + B increased significantly NPPL, NGPL and NGP. The NPPL, NGPL were significantly increased with 600 mL ha-1 of the inoculant. The dose of 600 mL ha-1 of the inoculant combined with Ca+B significantly stimulated NPPL, NGPL and NGP. It is concluded that the productivity of soybean was increased with addition of 600 mL ha-1 inoculant, in combination with Ca and B.